Chad Economic Update - April 2022 : Resilience in Uncertain Times - Harnessing Agriculture and Livestock Value Chains - World Bank (Washington, DC, 2022)
Chad’s gross domestic product (GDP) contracted by 1.2 percent in 2021 - the second consecutive year of recession - driven by a two-month suspension of oil production at its Esso plants, economic disruptions due to sociopolitical insecurity, and liquidity constraints because of delays in debt restructuring. Low oil revenue, coupled with increased spending to deal with shocks, widened the fiscal deficit to 4.3 percent of GDP in 2021. The 2022-24 economic recovery is expected to be fragile and subject to significant downside risks related to recurrent and emerging sources of vulnerability. With a slow and fragile economic recovery, the adverse effects of the pandemic on poor and vulnerable households are expected to last in the short to medium term. Chad can seize emerging opportunities offered by the political transition, increasing oil prices, and debt restructuring to undertake reforms aimed at renewing its social contract and reducing long-term vulnerabilities. Stronger agricultural and livestock value chains are critical to economic diversification, sustainable growth, and food security in the medium to long term. Livestock is the economy’s most important non-oil sector and represents a major income source in the agriculture sector. The government should take bold actions to strengthen or create agricultural and livestock value chains.